The impact of marketing innovations on the performance of Women-Owned Textile Businesses in Ernakulam District (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Women are more likely to operate their own businesses because of their individuality and strength of character. Female entrepreneurs have a leg up in the marketplace thanks to their innovative product ideas, which might be a reflection of their marketing success. As a fundamental component of market strategy, marketing performance is both a significant management problem and an essential component of company success. Women-Owned Textile Businesses in the Ernakulam District were the focus of this research, which aimed to examine how marketing innovations affected their performance.